Challenges in the Caesarean Section of a Severely Kyphotic Parturient - Manisha Chhetry; Basudeb Banerjee; Shanti Subedi; Narayan Bahadur Gharti Chhetri; Yogendra Gupta (Case Reports in Obstetrics and Gynecology)
Caesarean section in a severely kyphotic patient presents with unique challenges. We report a case of obstructed labor in case of a pregnant lady with severe kyphosis of spine that was managed by caesarean section. Lateral recumbent position with adequate assistance and paramedian or vertical skin incision was used and found to provide good exposure. Baby was delivered by lower segment uterine incision by reverse breech extraction. Postpartum hemorrhage was managed with uterotonics and bilateral uterine artery ligation. Tubal ligation though advised was refused by the patient. Prolonged catheterization was done in view of obstructed labor. Postoperative period was uneventful.